The Evaluation of Swimming Sports Coaching Programs for Disabled Athletes in The National Paralympic Committee - Utomo Utomo; Yetti Supriyati; Maruf Akbar (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Evaluation of swimming sports coaching programs for disabled athletes in the National Paralympic Committee (NPC) organization aims to assess the effectiveness of programs run by the South Kalimantan Province NPC by analyzing the role of each factor in accordance with the CIPP approach model. The CIPP model consists of four types of evaluations, namely: context evaluation, input evaluation, process evaluation. The data were analyzed using qualitative descriptive techniques. The results of the study were used for recommendations to all institutions/agencies/organizations in the field of sports in improving coaching for athletes with disabilities, especially in the field of swimming sports. Abstrak: Evaluasi program pembinaan cabang olahraga renang bagi atlet disabilitas pada organisasi National Paralympic Committee (NPC) bertujuan untuk mengkaji efektifitas program yang dijalankan oleh NPC Provinsi Kalimantan Selatan dengan menganalisis peran masing-masing faktor sesuai dengan model pendekatan CIPP. Model CIPP terdiri dari empat jenis evaluasi, yaitu: evaluasi konteks (context evaluation), evaluasi masukan (input evaluation), evaluasi proses (process evaluation). Data dianalisis menggunakan tehnik deskriptif kualitatif. Hasil penelitian dijadikan rekomendasi untuk bahan masukan kepada seluruh lembaga/instansi/organisasi bidang keolahragaan dalam meningkatkan pembinaan bagi atlet disabilitas, terutama dalam bidang olahraga renang.